2020
DOI: 10.18176/jiaci.0451
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Barcelona Olfactory Test ̶ 6 (pBOT-6): Validation of a Combined Odor Identification and Threshold Screening Test in Healthy Spanish Children and Adolescents

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Similar limited reliability of the identification test was found in children and adolescent populations with an intraclass correlation coefficient of 0.83 in the study by Marino‐Sanchez et al. [ 28 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar limited reliability of the identification test was found in children and adolescent populations with an intraclass correlation coefficient of 0.83 in the study by Marino‐Sanchez et al. [ 28 ].…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, in the Spanish validation of Sniffin' Sticks olfactory test (TDI), Delgado-Losada et al reported a moderate testretest reliability value of the identification test (r s = 0.69) using Pearson and intraclass coefficient correlation [26], while Haehner et al reported a value of 0.88 [27]. Similar limited reliability of the identification test was found in children and adolescent populations with an intraclass correlation coefficient of 0.83 in the study by Marino-Sanchez et al [28].…”
Section: Discussionmentioning
confidence: 82%
“…The advantages of the BOT-8 smell test are the short time needed for application (around 3 to 6 minutes) and the fact that it is easy-to perform and reusable. Recently, the pediatric Barcelona Olfactory Test-6 (pBOT-6), which includes an identification and threshold test and was validated for Spanish children, demonstrated high sensitivity and specificity for detecting hyposmia [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several of the previously described psychophysical tests are suitable for the paediatric population, aged as low as 5 years old. Specific adaptations for children include the ‘U-sniff’, adapted from the Sniffin’ Sticks, and the paediatric Barcelona Olfaction Test (pBOT-6) [ 36 , 37 ].…”
Section: Psychophysical Testingmentioning
confidence: 99%